2018
DOI: 10.1111/jcmm.13728
|View full text |Cite
|
Sign up to set email alerts
|

The expression of MMP‐1 and MMP‐9 is up‐regulated by smooth muscle cells after their cross‐talk with macrophages in high glucose conditions

Abstract: Patients with diabetes mellitus have an increased risk of myocardial infarction and coronary artery disease‐related death, exhibiting highly vulnerable plaques. Many studies have highlighted the major role of macrophages (MAC) and smooth muscle cells (SMC) and the essential part of metalloproteases (MMPs) in atherosclerotic plaque vulnerability. We hypothesize that in diabetes, the interplay between MAC and SMC in high glucose conditions may modify the expression of MMPs involved in plaque vulnerability. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…Bansal et al [ 38 ] reported that macrophages expressed MMP-9 after stimulation with phosphatidyl-myo-inositol dimannosides (PIM2) through PI3K and Notch1 signaling pathways. SMCs also exhibited augmented expression of MMP-9, increased MMP-9 enzymatic activity, and impaired function of collagen assembly upon cross-talk with macrophages in high glucose conditions [ 39 ]. In addition, Magid et al [ 40 ] found that the expression of MMP-9 in ECs is flow-sensitive and is upregulated by oscillatory flow via c-Myc activation.…”
Section: Molecular Architecture and Mmp-9 Regulationmentioning
confidence: 99%
“…Bansal et al [ 38 ] reported that macrophages expressed MMP-9 after stimulation with phosphatidyl-myo-inositol dimannosides (PIM2) through PI3K and Notch1 signaling pathways. SMCs also exhibited augmented expression of MMP-9, increased MMP-9 enzymatic activity, and impaired function of collagen assembly upon cross-talk with macrophages in high glucose conditions [ 39 ]. In addition, Magid et al [ 40 ] found that the expression of MMP-9 in ECs is flow-sensitive and is upregulated by oscillatory flow via c-Myc activation.…”
Section: Molecular Architecture and Mmp-9 Regulationmentioning
confidence: 99%
“…36 Tumor-derived MMP1 can activate endothelial PAR1 to induce the destruction of the vascular endothelial barrier and increases vascular permeability. 37,38 MMP1 has been demonstrated to be involved in developing insulin resistance and T2DM. Compared with the non-diabetic controls, MMP1 expression in vitreous specimens collected from patients with diabetic retinopathy was up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from endothelial and SMC, MMPs are also produced by infiltrating macrophages . Crosstalk between T cells, macrophages and SMCs can increase MMP production particularly in vulnerable plaques . MMPs are not only contributing to the destabilization of the plaque by degradation of collagen and other ECM proteins.…”
Section: Mmp Roles In Plaque Vulnerabilitymentioning
confidence: 99%